Characterization of Anthocyanins Including Acetylated Glycosides from Highbush Blueberry (Vaccinium corymbosum L.) Cultivated in Korea Based on UPLC-DAD-QToF/MS and UPLC-Qtrap-MS/MS - Ju Hyung Kim; Ryeong Ha Kwon; So Ah Kim; Hyemin Na; Jeong-Yong Cho; Heon-Woong Kim (Foods)
In this study, anthocyanin glycosides from nine cultivars of highbush blueberries grown in Korea were characterized using UPLC-DAD-QToF/MS and UPLC-Qtrap-MS/MS. A total of twenty-two derivatives were identified, consisting of mono-glycosides and acetyl-glycosides attached to aglycones, such as cyanidin, peonidin, delphinidin, petunidin, and malvidin. Among them, seven acetylated glycosides were tentatively determined by comparing the related authentic standards and previous reports and presented mass fragmentation, in which the acetyl group remained as the form attached to the sugar without de-esterification in positive ionization mode. The mid-season cultivar ‘New Hanover’ showed the highest total anthocyanin content (1011.7 mg/100 g dry weight) with predominant malvidin and delphinidin glycosides. Particularly, the ‘Patriot’ (early season) recorded the highest proportion of acetylated glycosides (19.7%). Multivariate analysis showed a distinct separation between early and mid-seasons with Draper. Especially, delphinidin 3-O-galactoside (VIP = 1.94) was identified as a marker for mid-season, and malvidin 3-O-glucoside (VIP = 1.79) was identified as a marker for early season. These comprehensive anthocyanin profiles of Korean blueberries will serve as fundamental data for breeding superior cultivars, evaluating and developing related products as well as clinical and metabolomic research.